Can carsharing meet the mobility needs for the low-income neighborhoods? Lessons from carsharing usage patterns in New York City. (July 2015) - Kim, Kyeongsu
Highlights: Research on micro-level carshare usage pattern for New York metropolitan region. Insignificant difference of carshare demand in relatively low-income neighborhoods. Higher demand for midsize vehicles than luxury or economy vehicles. Impact of weeknight's special rate on carshare usage in marginalized neighborhoods. Significance of the number of vehicles than the number of carshare locations. Abstract: For decades, carsharing has become an attentive dialogue among transportation planners and civic groups who have long supported and business owners and government officials who see carsharing as a means to realize their interests i.e., another market for revenue generation and replacement of government own vehicles with carshare units. It has particularly drawn attention in New York City (NYC). As of today, NYC is the largest carsharing market in the United States, accounting for about one third of all North American carsharing members. In addition to market-driven forces, the City government has pronounced pro-carsharing policies. Yet carsharing is still considered as an exclusive program to middle-income, white, and young populations. The purpose of this study is to see if carsharing can help meet the mobility demand for urban residents, especially in the marginalized neighborhoods. By investigating a leading carsharing program – Zipcar's vehicle utilization pattern in NYC, I attempt to disentangle how neighborhoods with different socio-demographics are associated with carsharing usage. The study result revealed that there is high demand for midsize (standard) vehicles on weekdays and weeknights. In addition, carsharing usage was highly correlated with the number of total vehicles, not the number of Zipcar parking lots, if the cars are accessible within walking distances. More importantly, carsharing in low-income neighborhoods did not differ from the typical carsharing locations. What matters is the affordability. Hence, there is no reason not to consider new services or expanding existing service boundaries to the outer boroughs in the future.